PREZIDENTO INSTITUTAS UŽSIENIO ŠALIŲ IR UKRAINOS VALSTYBĖS VALDŽIOS MECHANIZME - A., Šatilo V. V. (Teisė, 2014)
Статья посвящена характеристике правового института президента в современном мире. Рассмотрена история зарождения института президентства и его современные трансформации в зарубежных странах и в Украине. Приведена характеристика форм, правового положения института президента в различных странах, требований к кандидатам на пост президента, способов избрания президента, полномочий и форм ответственности президента. The legal institute of President in the contemporary times is highlighted. Rise of the institute of President and its most recent transformations in foreign countries are discussed. Characteristics of forms, legal status of the institute of President in various countries, criteria to candidates on this post, authorities and legal liability of President are outlined.